2018
DOI: 10.3892/or.2018.6435
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of cyclin F mRNA expression in the survival of skin melanoma patients: Comprehensive analysis of the pathways altered due to cyclin F upregulation

Abstract: Cyclin F is a part of the Skp, Cullin, F-box containing ligase complex. The activity of cyclin F includes cell cycle control, centrosome duplication and response to DNA damage. The cyclin F expression pattern is very similar to cyclin A, but cyclin F is an orphan cyclin without its cyclin-dependent kinase partner. There is little evidence concerning the role of cyclin F in cancer. In the present study, for the first time, we present analysis from The Cancer Genome Atlas (TCGA) data in the context of expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…In agreement with our studies, CCNF has been recently identified as an upregulated gene in primary pancreatic tumors from Ela-c-myc transgenic mice, compared to both normal pancreas and liver metastatic lesions [ 14 ]. In terms of clinical significance, the results obtained here are in line with our recent non-pancreas cancer in silico study, in which overexpression of CCNF mRNA was associated with a worse survival of melanoma patients [ 13 ]. Based on publicly available datasets, Liu et al have also shown that CCNF was positively correlated with the types of highly malignant and poor-prognostic breast cancer (BC), which had the features of low differentiation, high invasiveness, easy to metastasize, and relapse.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with our studies, CCNF has been recently identified as an upregulated gene in primary pancreatic tumors from Ela-c-myc transgenic mice, compared to both normal pancreas and liver metastatic lesions [ 14 ]. In terms of clinical significance, the results obtained here are in line with our recent non-pancreas cancer in silico study, in which overexpression of CCNF mRNA was associated with a worse survival of melanoma patients [ 13 ]. Based on publicly available datasets, Liu et al have also shown that CCNF was positively correlated with the types of highly malignant and poor-prognostic breast cancer (BC), which had the features of low differentiation, high invasiveness, easy to metastasize, and relapse.…”
Section: Discussionsupporting
confidence: 89%
“…Based on these findings, its role in controlling genome integrity through ubiquitin-mediated proteolysis has been proposed [ 8 , 9 , 10 , 11 , 12 ]. Despite its crucial nature and role in mitotic fidelity, the expression of this protein with respect to its prognostic significance in human cancers has hardly been studied, and most available articles, including our recent one [ 13 ], are based on in silico transcriptome data, but to our knowledge, none of the previous ones concerned the pancreatic cancer. Here, the analysis of TCGA dataset of 177 pancreatic adenocarcinoma patients showed that mRNA expression levels of CCNF were significantly elevated in 57.63% of PDACs and associated with more advanced and aggressive tumors and poor patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that CCNF controls tumorigenesis through IDH1-R132H [46]. High CCNF expression was associated with a poor outcome in melanoma patients [47]. An abnormal DLX4 expression level has been reported in inflammatory breast cancer, leukemia, lung cancer, ovarian cancer, and prostate cancer [48,49,50,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…CCNF, capable of forming Skp1‐Cul1‐F‐box protein ubiquitin ligase complex, is implicated in controlling centrosome duplication and preventing genome instability. Gagat, Krajewski, Grzanka, and Grzanka () revealed that high expression of CCNF in melanoma patients was associated with worse overall survival. Additionally, with gene network reconstruction, CCNF was regarded as one of the main drivers in cell cycle network in gastric cancer (Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%